Keberterimaan Instrumen Penilai Kompetensi Komunikasi dan Interaksi Positif Konselor Terhadap Masyarakat Sekolah - Sancaya, Setya Adi; Krisphianti, Yuanita Dwi; Hanggara, Guruh Sukma; Muzaki, M. Fauzan (Universitas Nusantara PGRI Kediri, 2019)
An important competency that must be possessed by the counselor is competence in communication and positive interaction with the school society. These skills include three things, namely with teaching staff, students, and students. From the dispute, there were no instruments that were eligible to get this ranking. The purpose of this research is to create a communication instrument of communication and positive interaction with the school society that has acceptance by experts and understanding. This research method is development research. Research subjects were two experts from academia and two experts from guidance and counseling. The results of the study with the subject of two academic experts are 0.34 with quite good/decent enough criteria. Results from research with expert research subjects 0.36 with the criteria quite good/decent enough. The conclusion from this study shows that the assessment instrument of communication competence and positive counselor interaction with the school society has had a good acceptance from experts and conversions. From the findings, the researcher provides suggestions: 1) before applying the instrument, the researcher needs to provide an understanding in the form of a direct explanation to the BK teacher on the function of the BK performance evaluation instrument; 2) the researcher should develop instruments using easy to understand language, straightforward and simple sentences, and the sentence is not too long; 3) in further research it is necessary to further develop the results of this research in the form of applicable technology.